Design and evaluation of a web-based learning module on computer networking - Hashim, Sulaiman (IGI Global, 2012)
The Malaysian Secondary School lnformation Technology (IT) curriculum introduced in 1999 was developed based on the Smart School's framework which emphasized on the use of self-directed,self-access,self-assess and self-pace learning methodologies.However, the introduction of the online IT self-learning module that was supposed to helps teachers in adopting this methodology has not been implemented well. As a result, teachers tend to revert to their traditional teaching approaches which could jeopardize the success of the IT curriculum's objectives. This study was carried out to design, develop and evaluate a new web-based learning module which the researcher hopes could improve or possibly replace the existing module.